Development of genotyping method for functionally relevant variants of cytochromes P450 in cynomolgus macaques. Issue 1 (28th July 2017) - Uno, Y.; Osada, N.; Sakurai, S.; Shimozawa, N.; Iwata, T.; Ikeo, K.; Yamazaki, H.
Abstract : In cynomolgus macaques ( Macaca fascicularis ), widely used in drug metabolism studies, CYP2C9, CYP2C76, CYP2D6, CYP3A4, and CYP3A5, important drug‐metabolizing enzymes, are abundantly expressed in liver and metabolize cytochrome P450 substrates. CYP2C9 (c.334A>C), CYP2C76 (c.449TG>A), CYP2D6 (c.891A>G), CYP3A4 (IVS3 + 1G>del), and CYP3A5 (c.625A>T) substantially influence metabolic activity of enzymes, and thus are important variants in drug metabolism studies. In this study, a real‐time PCR method was developed for genotyping these variants. The validity of the methods was verified by genotyping two wild type, two heterozygous, and two homozygous DNAs and was used to genotype 41 cynomolgus macaques (from Cambodia, Indonesia, the Philippines, or Vietnam) for the five variants, along with another important variant CYP2C19 (c.308C>T). The CYP2C9 and CYP2C19 variants were found only in Cambodian and Vietnamese animals, while the CYP2C76 and CYP2D6 variants were found only in Indonesian and Philippine animals. The CYP3A4 and CYP3A5 variants were not found in any of the animals analyzed. Mauritian animals, genotyped using next‐generation sequencing data for comparison, possessed the CYP2C19 and CYP2D6 variants, but not the other variants. These results indicated differences in prevalence of these important variants among animal groups. Therefore, the genotyping tool developed is useful for drug metabolism studies using cynomolgus macaques.